2011
DOI: 10.1108/07378831111138152
|View full text |Cite
|
Sign up to set email alerts
|

How can educational technology facilitate student engagement with online primary sources?

Abstract: PurposeThe authors received a grant to develop a digital educational tool to facilitate student engagement with online primary sources. Students and faculty were interviewed prior to developing the tool's specifications to ensure a user‐centered focus. This research paper seeks to report the results of a user needs assessment that explored students' use of primary sources and their learning preferences, as well as faculty's pedagogical goals for student work with primary sources.Design/methodology/approachFacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
1
18
1
7
Order By: Relevance
“…26 This correlates with findings that generation Y students prefer to study and learn using audiovisual materials over textual information. 27 This is a good illustration of the benefit of using multiple teaching methods to satisfy various student learning styles, which is in line with previous research showing that one of the advantages of e-tools is to present information to students in different ways, thereby catering to individual learning styles. 28 Student feedback indicated that supplementing lectures with e-tools in the Human Pharmacology courses gave them the flexibility to choose the learning method that best suited their needs.…”
Section: Discussionsupporting
confidence: 67%
“…26 This correlates with findings that generation Y students prefer to study and learn using audiovisual materials over textual information. 27 This is a good illustration of the benefit of using multiple teaching methods to satisfy various student learning styles, which is in line with previous research showing that one of the advantages of e-tools is to present information to students in different ways, thereby catering to individual learning styles. 28 Student feedback indicated that supplementing lectures with e-tools in the Human Pharmacology courses gave them the flexibility to choose the learning method that best suited their needs.…”
Section: Discussionsupporting
confidence: 67%
“…According to Quinsee and Bullimore two factors include operations and resource planning, can be considered as educational activities related to faculty (Quinsee & Bullimore , 2011). Another factor to create a positive academic experience is "primary sources" (Lindquist & Long , 2011);they have expressed digital primary sources have a…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the problems humanities researchers encounter in utilizing these collections, researchers conducted 21 semi-structured interviews with CU faculty and students [15]. The major user needs identified were better support for: 1) locating documents and data relevant to a particular topic within distributed online collections; and 2) contextualizing the content, for instance, to gauge author bias or simply become familiar with the places, events, and people mentioned in the documents.…”
Section: Reasons For Creating the Datasetmentioning
confidence: 99%